Grazing effects on soil organic carbon stocks of German salt marshes along the Baltic Sea and North Sea coast - Ella Logemann; Clarisse Gösele; Hannah Hosbach; Kathryn Nicol; Kai Jensen; Peter Müller (PANGAEA, 2025)
In order to assess grazing effects in soil organic carbon (SOC) stocks, three distinct salt marsh types were sampled: Baltic Sea salt marshes, North Sea mainland salt marshes and North Sea island salt marshes. Between 2022 and 2023, eight study sites were sampled, with transects laid out across the two management types (grazed and non-grazed), each management site at comparable successional stages. In each study site 6-10 plots were assessed. For the quantification of SOC content, soil bulk density and SOC δ13C signature, a single 30-cm soil core was taken from each plot. An Eijkelkamp peat sampler was used for taking soil cores. Dry soil bulk density was calculated from sample dry weight and volume. Prior to elemental and isotope analysis, macroscopic root residues were removed and soil samples were acidified.